The Dance of Change. Staff and User - Jouly, Hannelore (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
In the beginning I would like you to imagine a picture: there are people lying in deckchairs, young, cultivated, relaxed, surrounded by books. Are this the staff of the library thinking up ways of making the Stuttgart City-Library more attractive? Or are this the customers, who dream of their ideal library, which is open all day and all night, providing access to the global data networks and housing all the books you could possibly want to read, a library whose staff are highly competent and unshakably charming, a library with an inspiring and relaxed environment?